2014
DOI: 10.5603/kp.2013.0181
|View full text |Cite
|
Sign up to set email alerts
|

The presence of fragmented QRS on 12-lead ECG in patients with coronary slow flow

Abstract: A b s t r a c tBackground: Coronary slow flow (CSF) is characterised by delayed opacification of coronary arteries in the absence of epicardial occlusive disease. It has been reported that CSF may cause angina, myocardial ischaemia, and infarction. Fragmentation of QRS complex (fQRS) is an easily evaluated non-invasive electrocardiographic parameter. It has been associated with alternation of myocardial activation due to myocardial scar and/or ischaemia. Whether CSF is associated with fQRS is unknown. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…1,2 Correlation and prognostic importance of presence of fQRS on ECG have been shown in various cardiovascular diseases such as cardiomyopathy, coronary slow flow, left ventricular noncompaction, and Brugada syndrome. [3][4][5][6][7] In addition, various studies have evaluated the prognostic importance of fQRS in patients with acute coronary syndrome (ACS), ST-segment elevation (STEMI), or non-ST segment elevation myocardial infarction (NSTEMI). [8][9][10][11][12][13][14][15][16][17][18] Some recent papers reviewed the clinical importance of fQRS in patients with cardiovascular diseases.…”
mentioning
confidence: 99%
“…1,2 Correlation and prognostic importance of presence of fQRS on ECG have been shown in various cardiovascular diseases such as cardiomyopathy, coronary slow flow, left ventricular noncompaction, and Brugada syndrome. [3][4][5][6][7] In addition, various studies have evaluated the prognostic importance of fQRS in patients with acute coronary syndrome (ACS), ST-segment elevation (STEMI), or non-ST segment elevation myocardial infarction (NSTEMI). [8][9][10][11][12][13][14][15][16][17][18] Some recent papers reviewed the clinical importance of fQRS in patients with cardiovascular diseases.…”
mentioning
confidence: 99%
“…The presence of fQRS was demonstrated to be an independent predictor of decreased myocardial perfusion and left ventricular function in patients with ischemic heart disease . Moreover, fQRS, which may be widened or narrowed, has been reported to be related with high mortality and morbidity, including hemodynamically significant arrhythmic events in coronary artery disease, coronary slow flow, acute coronary syndromes, ischemic and nonischemic cardiomyopathies, hypertrophic obstructive cardiomyopathy, and decompensated systolic heart failure . In this study, the predictive value of admission fQRS complex for in‐hospital adverse cardiovascular events in patients with a type 1 AAD was investigated.…”
Section: Discussionmentioning
confidence: 76%
“…The presence of fQRS was demonstrated as an independent predictor of decreased myocardial perfusion and left ventricular function in patients with ischemic heart disease . Furthermore, the prognostic predictive value of fQRS for other cardiovascular diseases has also been reported …”
mentioning
confidence: 91%
“…They found that fQRS is significantly more found in patients with isolated CAE than in patients with normal coronaries [39]. fQRS is more frequently seen in patients with slow coronary flow which is an indicator of microvascular dysfunction [40]. This association between fQRS and coronary slow flow was discussed in some studies as that was done by Mittal [41].…”
Section: Discussionmentioning
confidence: 96%